Effect of regulated deficit irrigation on tree growth of pear cv. Triumph of Vienna (2015)
The deficit irrigation controlled (RDI) as reducing water in phases of the crops where it is less sensitive to water stress, three different drip irrigation treatments were applied in pear tree crop of Triunfo de Viena variety. Control, irrigated throughout the year at 100% of estimated crop evapotranspiration (ETc); 67%ETc and 55%ETc treatments were irrigated at 67 and 55% of the (ETc), respectively during the period of rapid fruit growth (from December 28, 2011 until February 29, 2012) and at 100% (ETc) during the rest of the season. Reference evapotranspiration (ETo) was determined by the Penman-Monteith, with hourly weather data collected in a nearby meteorological station. During the test total precipitation was 53.8 mm and the water application in the control treatments was 683.0 mm. The results indicate that none of the treatments differed significantly (P≤0.05) from control in terms of yield and quality, resulting in water savings of 33 to 45% in 67%ETc and 55%ETc respectively compared to the control. The vegetative growth of shoots had a behavior defined by a sigmoid curve fitted to a four parameter logistic equation, and it was significantly reduced in the 67%ETc and 55%ETc, respect to control, at the end of the restriction.